CONSERVATISM IN INVENTORY VALUATION. - Scott, D. R. (The Accounting Review, 1926)
Abstract The conduct of business enterprise is the source from which accounting theory takes its rise. When business enterprise worked with relatively undeveloped resources and through a relatively undeveloped technique of production, the circumstances of its operation were comparatively unstable. The conduct of enterprise did not run in exact terms. Managers had to be satisfied with approximations. But in modern times a high degree of technological development has been accompanied by an increasing size and complexity of business organization. Management has come to Include coordination of a great variety of activities. Business control has come to rest upon exact management and appraisal of both business and technological facts. If it is true as above stated that accounting does develop out of practical business administration affairs, then this fundamental changes in the circumstances of business administration should be reflected in accounting technique. Accounting theory grew up as a body of rules or principles governing the application of double entry technique to the affairs of business enterprises. But as business administration has changed in character an accompanying change has taken place in the technique used by it. Much statistical technique not included in the double entry record has made its appearance in the accounting system.